Bibliography of Phasmida (Insecta) - VIII. Supplement I (1930-1984). - Carlberg, Ulf (Contributions to Entomology = Beiträge zur Entomologie, 1994)
The literature on the stick- and leaf-insects (order Phasmida) published during the period 1930-1984, which previously has been missed, has now been listed. A total of 109 scientific papers, chapters in books, thesises, reports etc. are listed. A systematic index is included.